No Relationship Between Patent Foramen Ovale and Migraine Frequency. Issue 9 (16th September 2016) - Larrosa, Davinia; Ramón, César; Alvarez, Rocío; Martínez‐Camblor, Pablo; Cernuda, Eva; Pascual, Julio
Abstract : Background: Pathophysiology of migraine is not fully known. A link has been proposed between migraine and patent foramen ovale (PFO). However, there are conflicting data regarding the causal relationship between PFO and migraine. Objective: To test a potential association between migraine frequency and PFO by way of an observational, single‐center, case‐controlled study. Methods: We studied a total of 130 chronic migraine (CM) and 53 episodic migraine (EM) patients. Transcranial Doppler with agitated saline injection was used to evaluate the presence and degree of PFO. PFO was judged to be present if any signal was detected. The degree of PFO during rest and Valsalva was quantified as follows: small (1–10 microbubbles [MB]), medium (10–25 MB), or large (>25 MB with shower or curtain pattern). PFO detected at rest were considered permanent, while those detected during Valsalva maneuver were classified as latent. Results: The prevalence of PFO was similar in CM and EM patients (53.1% [44.1–62.2] vs 54.7% [40.3–69.1], P  = .871). PFO size was significantly larger in the EM group compared to the CM group (35.8% vs 20.3%, P  = .037). The presence of permanent PFO was also significantly higher in EM compared to CM (37.7% vs 22.7%, P  = .044). No differences were found according to the presence of aura. Conclusion: This study indicates that PFO is not more common or larger in CM than in EM patients. These findings do not support a relationship between PFO and migraine frequency.